Cauchy problem for one class of pseudodifferential systems with entire analytic symbols - Litovchenko, V. A.; Літовченко, В. А. (Institute of Mathematics, NAS of Ukraine, 2006)
Using functions convex downward, we describe a class of pseudodifferential systems with entire analytic symbols that contains Éidel’man parabolic systems of partial differential equations with continuous time-dependent coefficients. We prove a theorem on the correct solvability of the Cauchy problem for these systems in the case where initial data are generalized functions. We also establish the principle of localization of a solution of this problem.